2013
DOI: 10.1007/s11467-013-0306-z
|View full text |Cite
|
Sign up to set email alerts
|

Black hole binaries and microquasars

Abstract: This is a general review on the observations and physics of black hole X-ray binaries and microquasars, with the emphasize on recent developments in the high energy regime. The focus is put on understanding the accretion flows and measuring the parameters of black holes in them. It includes mainly two parts: (1) Brief review of several recent review article on this subject; (2) Further development on several topics, including black hole spin measurements, hot accretion flows, corona formation, state transition… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
55
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 175 publications
(241 reference statements)
0
55
0
3
Order By: Relevance
“…However, the hysteretic state transition in XRBs, i.e., the transition of the low/hard state to thermal state occurs at a luminosity much higher than that for the transition from the thermal state to low/hard state (e.g., Miyamoto et al 1995;Zhang et al 1997;Nowak et al 2002;Maccarone & Coppi 2003;Zdziarski et al 2004;Yu et al 2004;Yu & Yan 2009), is still not well understood in the frame of the above mentioned scenarios (see, e.g., Zhang 2013, for a review). In most of the previous models, the accretion mode transition is solely triggered by the dimensionless mass accretion rate (see, e.g., Narayan et al 1998;Yuan & Narayan 2014, for reviews).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the hysteretic state transition in XRBs, i.e., the transition of the low/hard state to thermal state occurs at a luminosity much higher than that for the transition from the thermal state to low/hard state (e.g., Miyamoto et al 1995;Zhang et al 1997;Nowak et al 2002;Maccarone & Coppi 2003;Zdziarski et al 2004;Yu et al 2004;Yu & Yan 2009), is still not well understood in the frame of the above mentioned scenarios (see, e.g., Zhang 2013, for a review). In most of the previous models, the accretion mode transition is solely triggered by the dimensionless mass accretion rate (see, e.g., Narayan et al 1998;Yuan & Narayan 2014, for reviews).…”
Section: Introductionmentioning
confidence: 99%
“…However, the advection of the field in a geometrically thin (H R 1  ) is inefficient due to its small radial velocity. The magnetic diffusion timescale is about the same as the viscous timescale in a steady disk, which leads to a very weak radial field component at the surface of a thin disk (Lubow et al 1994), though some specific mechanisms were suggested to alleviate the difficulty of field advection in thin disks (Spruit & Uzdensky 2005;Lovelace et al 2009;Guilet & Ogilvie 2012, 2013Cao & Spruit 2013). The vertical field can be dragged efficiently by an ADAF (Cao 2011), because the radial velocity of ADAFs is much larger than that of a thin accretion disk (Narayan & Yi 1994.…”
Section: Introductionmentioning
confidence: 99%
“…It includes active galactic nuclei (AGNs, H. Krawczynski and E. Treister) [1] that host super-massive black holes, stellar-size black hole X-ray binaries (BHXBs, S.-N. Zhang) [2], gamma-ray bursts (GRBs, N. Gehrels and S. Razzaque) [3], and various species in the neutron star (NS) zoo (A. K. Harding) [4]. The 5th planned article on supernovae and their remnants did not materialize.…”
Section: Pacs Numbersmentioning
confidence: 99%
“…In particular, magnetic reconnection between the magnetospheric lines of the central source and those anchored into the accretion disk resulting in the ejection of plasmons has been detected in numerical MHD studies by (see, e.g., Romanova et al 2002Romanova et al , 2011Zanni & Ferreira 2009, 2013Čemeljić et al 2013). The recent numerical relativistic MHD simulations of magnetically arrested accretion disks by Tchekhovskoy et al 2011;McKinney et al 2012;Dexter et al 2014 also evidence the development of magnetic reconnection in the magnetosphere of the BH and are consistent with our scenario above.…”
Section: Introductionmentioning
confidence: 98%
“…Fast reconnection has recently gained increasing interest also in other astrophysical contexts beyond the solar system because of its potential efficiency to explain magnetic field diffusion, dynamo process, and particle acceleration in different classes of sources and environments -from compact objects, like BHs (e.g., GL05, GL10, Giannios 2010), pulsars (e.g., Cerutti et al 2013Cerutti et al , 2014Sironi & Spitkovsky 2014), and gamma ray bursts (e.g., Zhang & Yan 2011), to more diffuse regions like the interstellar medium (ISM), intergalactic medium (IGM), and star forming regions (e.g., Santos-Lima et al 2010, 2013Leão et al 2013; see also Uzdensky 2011;de Gouveia Dal Pino & Kowal 2015;de Gouveia Dal Pino et al 2014 and references therein for reviews).…”
Section: Introductionmentioning
confidence: 99%